Mechanical Ocular Trauma : Current Consensus and Controversy - Yan, Hua (Springer Singapore : Imprint: Springer, 2017)
This book provides state-of-the-art information for ophthalmologists and other clinicians facing tough cases, helping them to make the most appropriate decision concerning the management of patients who have suffered mechanical ocular trauma. The discussion of mechanical ocular trauma addresses various parts of the eye: each chapter discusses a certain part of the eye, supplemented by illustrative sample cases. Though the latest consensus is provided for each topic or case, different opinions on controversial topics will also be discussed in detail. Pearls of advice at the end of each chapter highlight its main points. Topics covered include: Traumatic cataract and the timing of surgery and IOL implantation, Traumatic hypotony, Traumatic glaucoma, Timing of vitrectomy after primary repair, Use of silicone oil in traumatic eyes, Intraocular foreign bodies, Traumatic endophthalmitis, and much more. As a topic-based clinical reference work on mechanical ocular trauma bringing together consensus and controversies, the book offers useful and attractive information for ophthalmologists and other readers. Hua Yan is a professor and chairman at the Department of Ophthalmology and the secretary of Tianjin Medical University General Hospital, Tianjin, China.
Keywords: Medicine.; Ophthalmology.; elektronické knihy; electronic books